Design EMI filter using Multi-Objective Optimization for Mitigation of Conducted Noise at Photovoltaic System - F. BEGGAT; F. BOUCHAFAA (University of Eloued جامعة الوادي, 2019)
Abstract—Electromagnetic interference (EMI) generated in a photovoltaic (PV) system issue has become one of the extremely important problems to be solved. It is well known that the inverter used in PV system is major sources of conducted disturbances which are the common mode and differential mode. Often, the solution used to reduce conducted emissions consists to use the EMI filters. In some cases, EMI filter assemblies require up to 40% of the total installation space of an inverter. These mechanisms lead to increasingly tougher demands on filter assemblies in terms of insertion loss and volume. To solve this problem, an automatic design optimization tool based on a co-simulation MATALB and LT- SPICE oriented at obtaining high performing EMI filters with the minimum volume and filter attenuation. A Database information of commercially available passive components (e.g. magnetic cores, capacitors), this last one allowed feed the program of design under MATLAB. Finally, the final phase allowed validating the filter performance with a temporal solver and frequency under LT-SPICE. Simulation and experimental results give a firm support to the proposed method.
Intervention
Keywords: Keywords—Electromagnetic interference; Automatic Design EMI filter; Multi-Objective Optimization; Conducted emissions Photovoltaic inverter; Parasitic elements; Filter attenuation.